Do Homeowners Increase Consumption after the Last Mortgage Payment? An Alternative Test of the Permanent Income Hypothesis - Coulibaly, Brahima; Li, Geng (The Review of Economics and Statistics, 2006)
The maturity date of a mortgage loan marks the end of monthly mortgage payments for homeowners. In the period after the last payment, homeowners experience an increase in their disposable income. Our study interprets this event as an anticipated increase in income, and tests whether households smooth consumption over the transition period as predicted by the rational-expectation life-cycle–permanent-income hypothesis. We find households do not alter nondurable-goods consumption in the period following the last mortgage payment. Instead, they increase both financial savings and savings in durable goods such as house furnishings and entertainment equipment in the year of the last mortgage payment.